UPAYA MENINGKATKAN KOMPETENSI GURU MELALUI PENDAMPINGAN PEMBUATAN VIDEO PEMBELAJARAN DI SD MUHAMMADIYAH BENJENG - Muyasaroh, Muyasaroh; Kolidah, Fida Nur; Adeliyah, Nadiyah Syifa; Mahfud, Choirul (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The world of education always moves dynamically following the changing times and conditions. Increasingly sophisticated technological advances should facilitate the world of education in learning. In addition, the condition of the Covid-19 pandemic that has hit the community requires students to go to school online. Based on this, teachers are required to improve pedagogical competence, especially making instructional videos as an artistic tool in the process of teaching activities. A teacher should have pedagogical competence, namely the art of class management that includes strategies in learning. or Oriented to the above problems, the community service team collaborates with service partners, namely the principal and teachers of SD Muhammadiyah Benjeng to assist in making learning videos. The purpose of this service is so that teachers at SD Muhammadiyah Benjeng can make creative and innovative learning videos. The method used in this mentoring is lesson study through 3 stages including plan, do and see (reflection). The result of this service is realizing teacher competence, namely that the teacher is independently able to make learning media in the form of instructional videos so that teaching and learning activities at SD Muhammadiyah Benjeng can be carried out effectively and pleasantly even though the school is online or online.